Fully automated dried blood spot sample handling and extraction for serological testing of SARS‐CoV‐2 antibodies. Issue 1 (4th November 2020) - Gaugler, Stefan; Sottas, Pierre‐Edouard; Blum, Katharina; Luginbühl, Marc
Abstract: At the beginning of 2020, an outbreak of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) reached pandemic dimensions. Throughout the event, diagnostic tests function as an essential tool for understanding, mitigating, and implement strategies to curb and reduce infections. Here, we present a novel method for the fully automated dried blood spot (DBS) sample handling and extraction for serological testing of human IgG antibodies against SARS‐CoV‐2 using a commercial enzyme‐linked immunosorbent assay (ELISA) testing kit. This proof‐of‐principle pilot study successfully demonstrates the recovery of antibodies in their intact form from DBS using automated, direct sample elution within 100 μl of extraction buffer. The use of minimally invasive DBS sampling provides an alternative to existing analytical procedures such as sampling by venipuncture or nasal swabs. Due to the ease of DBS collection, no third party need be involved, making at‐home sampling possible (e.g., during quarantine).